Reconstruction of Law Central Bank Digital Currency (CBDC) in Indonesia - Jati, Ridho Bawana; Yuspin, Wardah; Budiono, Arief (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The current era of digitalization has made everything digital, including currency. Other countries' currencies have implemented a Central Bank Digital Currency (CBDC) or an official digital currency issued by a central bank, such as El Salvador, Bahamas, China and Nigeria. The background to this research is that until now, there has been no precise legal regulation for using this digital currency in implementing CBDC use in Indonesia, even though the digital currency has been implemented in several countries, as mentioned above. This research uses qualitative research methods by implementing the use of CBDC in Indonesia and examining relevant legislation using it. The next stage uses comparative techniques with several countries, namely Bahamas, China, and Nigeria. The results of this research found that CBDC in Indonesia still needs to have legal regulations or laws that clearly regulate the implementation of CBDC. Rules regarding this use Law Number 7 of 2011 concerning Currency. However, the issuance of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (UU P2SK) opens up opportunities for the issuance of CBDC. Apart from that, Bank Indonesia also launched a project called White Paper "Garuda Project". According to the project, CBDC will be issued in 2025, which increases the chances of CBDC being issued in Indonesia.